Ease of Business Licensing Based on the Job Creation Law (Study of Public Participation in Preparation of AMDAL Document) - Sopian, Maskun (Universitas PGRI Madiun, 2023)
The omnibus law of the Job Creation Act changes several laws and regulations, including Law Number 32 of 2009 concerning Environmental Protection and Management (UU PPLH). This study found that changes in provisions related to Environmental Impact Analysis (Amdal) in Law No. 11 of 2020 concerning Job Creation, with those previously regulated in Law No. 32 of 2009 concerning Environmental Protection and Management. Such as the definition of Amdal, the role of environmental observers, the elimination of objections and community involvement, the Amdal Assessment Commission, the Feasibility Test Team, and cancellation based on court decisions. This research is normative legal research that examines in detail library materials such as books, scientific journals, laws and other information that is considered related to this research. This study argues that public participation in the preparation of the Amdal document must be carried out by the initiator and the government considering that public participation is the obligation of the initiator and the government in addition to being a good right of the community.